Fungsi komunikasi, faktor perubahan sikap aktor dan kefahaman ibu bapa terhadap video penyalahgunaan dadah di youtube - Mohamad I'rfan, Shahruddin (2022)
The issue of drug abuse in the community especially among teenagers extremely alarming and proliferation of information on social media can be easily accessed. YouTube plays its role as a medium of information dissemination in an effort to overcome the issue of drug abuse through the exposure of various forms of video. Thus, objectives of this research are identifying communication functions in the video’s view of drug abuse on YouTube, explaining the factors influencing attitude change based on drug abuse videos on YouTube, and analyzing parents’ understanding of drug abuse messages based on video views on YouTube. This research is qualitative in nature using qualitative content analysis and semi-structured interview. To achieve the first and second research objectives, the content analysis method was selected by analyzing three drug abuse videos on YouTube. Secondly, the semi-structured interviews were conducted with parents to support the findings of the qualitative content analysis and achieve the third research objective. The data were analyzed using QSR NVivo 12 software via thematic analysis technique. The results showed that there were five functions of communication in the selected drug abuse videos, namely persuasion in the form of warnings, conveying information, fostering awareness, educating, and entertainment. The factors influencing the attitude change featured in the video consisted of four factors namely motivation to change, community involvement, support of family members, and family conflict. Parents’ understanding of function of communications and factors influencing attitude change based on drug abuse video display consists of persuasion in the form of warnings, conveying information, raising awareness, educating the community to stay away from drugs, educational entertainment, YouTube as a source of motivation, family support, community involvement, a negative environment, and YouTube can influence user attitudes. This research explains to the community about the function of communication, factors that influence the attitudes of individuals involved in the drug abuse, and parents’ understanding of drug issues.